2011
DOI: 10.1002/esp.2159
|View full text |Cite
|
Sign up to set email alerts
|

Downstream effects of impounding a natural lake: the Snake River downstream from Jackson Lake Dam, Wyoming, USA

Abstract: A sediment mass balance constructed for a 16-km reach of the Snake River downstream from Jackson Lake Dam (JLD) indicates that river regulation has reduced the magnitude of sediment mass balance deficit that would naturally exist in the absence of the dam. The sediment budget was constructed from calibrated bed load transport relations, which were used to model sediment flux into and through the study reach. Calibration of the transport relations was based on bed load transport data collected over a wide ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
1
22
1
Order By: Relevance
“…[]; 2 = Erwin et al . []; 3 = Jones and Seitz []; 4 = Ryan and Emmett []; 5 = Hortness and Berenbrock []; 6 = Clark and Woods []; 7 = Williams and Krupin []; 8 = USGS National Water Information System accessed between 1/2008 and 7/2011; 9 = determined from field measurements by the authors; 10 = Berenbrock and Tranmer []; 11 = Kondolf et al . []; 12 = bankfull discharge estimated from a regional relationship as Q = a DA b , where Q is discharge, DA is drainage area, and a and b are empirical power law parameters; 13 = Miller []; 14 = Holnbeck []; 15 = Curran et al .…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…[]; 2 = Erwin et al . []; 3 = Jones and Seitz []; 4 = Ryan and Emmett []; 5 = Hortness and Berenbrock []; 6 = Clark and Woods []; 7 = Williams and Krupin []; 8 = USGS National Water Information System accessed between 1/2008 and 7/2011; 9 = determined from field measurements by the authors; 10 = Berenbrock and Tranmer []; 11 = Kondolf et al . []; 12 = bankfull discharge estimated from a regional relationship as Q = a DA b , where Q is discharge, DA is drainage area, and a and b are empirical power law parameters; 13 = Miller []; 14 = Holnbeck []; 15 = Curran et al .…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…The Snake River is regulated by Jackson Lake Dam, but wood and coarse bed material delivered from tributaries produce a wandering, frequently changing channel (Erwin et al. ; Nelson et al. ).…”
Section: Study Areasmentioning
confidence: 99%
“… Mueller et al [2005], however, noted that uncertainties in specifying a single critical shear can lead to large errors since the process is nonlinear. This estimate can be made using statistical methods, but it is not uncommon to adjust it by eye [ Erwin et al , 2011; Gaeuman et al , 2009; Wilcock et al , 2003; Mueller et al , 2005; Wilcock et al , 2009; Wilcock , 1988] because of some nonlinear regression techniques giving too much weight to observations far from critical (see Wilcock [1988] for a discussion on this). Additionally, Buffington and Montgomery [1997] compiled data from eight decades of incipient motion studies and created lists of reported critical shear values.…”
Section: Introductionmentioning
confidence: 99%